Molecular Reassessment of the Khawia sinensis (Cestoda: Caryophyllidea) Species Complex Reveals a New Species in Common Carp (Cyprinus carpio) - Doğan, Sibel; Sağlam, Naim (Central Fisheries Research Institute, 2026)
Khawia species are significant pathogens causing khawiasis in cyprinids, leading to substantial economic losses in aquaculture. Current literature suggests that Khawia sinensis represents a complex of multiple distinct species. To resolve this taxonomic ambiguity, we examined 93 parasite samples from three Cyprinus carpio populations in eastern Türkiye using an integrated morphological and molecular approach. Phylogenetic relationships were inferred using Maximum Likelihood, Bayesian Inference, and species delimitation analyses based on COX1 mtDNA, NAD3, and 18S rDNA. A new species, Khawia anatolica n. sp., is described from Karakaya, Keban, and Hazar Lakes, exhibiting high phylogenetic divergence at COX1 (~14–64%) compared to other Khawia species. Distinguishing morphological features, including a less wavy scolex and unique internal anatomy, separate K. anatolica n. sp. from previously described taxa. Species delimitation analyses confirmed that K. sinensis comprises multiple distinct species and that K. anatolica n. sp. forms a separate evolutionary branch. The mean abundance, intensity, and prevalence of K. anatolica n. sp. in C. carpio were 1.55 (1.1–2.4), 6.64±3.56 (2–15), and 23.33% (15–35%), respectively. This study advances understanding of parasitic diversity in Eastern Anatolian water resources and highlights the need to re-evaluate the taxonomic status of the K. sinensis complex. © 2026, Central Fisheries Research Institute. All rights reserved.
Keywords: Cyprinidae; Khawiasis; Molecular taxonomy; Phylogeny; Species delimitation